2008
DOI: 10.1007/s11771-008-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of quench transfer time on microstructure and mechanical properties of 7055 aluminum alloy

Abstract: The influence of quench transfer time on the microstructure and mechanical properties of 7055 aluminum alloy with and without zirconium was investigated by tensile properties test, optical microscopy, scanning electron microscopy and transmission electron microscopy. For the Zr-free alloy, the strength increases to the highest value at 20 s with transfer time, and then decreases slightly. The elongation decreases slowly with transfer time within 20 s, and more rapidly after 20 s. For the Zr-containing alloy, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…But this change due to slow quenching is limited to the grain boundary zone, and not observed inside grains far from grain boundaries. This kind of microstructure results in only slight drop in the strength of a wrought AlZnMgCu alloy without Zr after delayed quench, as shown in a previous paper [23]. In the homogenized and hot-rolled 7055-0Zr alloys and the homogenized 7055-0.15Zr alloy, the grains are large and the size is similar, thus, the quench sensitivity is low and the drop in the hardness due to slow quenching is similar (Fig.…”
Section: Effect Of (Sub)grain Boundaries On Quench Sensitivitysupporting
confidence: 77%
“…But this change due to slow quenching is limited to the grain boundary zone, and not observed inside grains far from grain boundaries. This kind of microstructure results in only slight drop in the strength of a wrought AlZnMgCu alloy without Zr after delayed quench, as shown in a previous paper [23]. In the homogenized and hot-rolled 7055-0Zr alloys and the homogenized 7055-0.15Zr alloy, the grains are large and the size is similar, thus, the quench sensitivity is low and the drop in the hardness due to slow quenching is similar (Fig.…”
Section: Effect Of (Sub)grain Boundaries On Quench Sensitivitysupporting
confidence: 77%
“…In addition, retrogression and re‐aging (RRA) treatment has been used to increase the resistance to stress corrosion cracking (SCC) of the 7xxx series alloys since the 1970s, which modified the size distribution, nearest neighbor distance and chemistry of the GBPs . Therefore, we can expect that the corrosion resistance would be improved by prolonging quench transfer time according to the observations of You et al . The above deducing, however, apparently contradicts the general opinions that a slow quench rate is more detrimental on IGC resistance .…”
Section: Introductionmentioning
confidence: 98%
“…Similar application also can be found in Huang ' s work , which referred to a high‐temperature pre‐precipitation (HTPP) process. Quench transfer time, namely delay during quenching, is an important quench parameter in industrial production, but it has rarely been considered, although You et al made a research on the influence of quench transfer time on the mechanical properties of the 7055 alloy. They found that the size and distance of the precipitates on grain boundary increased with prolonging transfer time, and the strength and elongation decreased slowly with transfer time within 20 s.…”
Section: Introductionmentioning
confidence: 99%
“…7075 is an aluminum-zinc-magnesium alloy that has a liquidus temperature of 635 o C and a solidus temperature of 477 o C, and the primary strengthening phase for the alloy is the eta phase, Zn2Mg [1,4]. The kinetics of this strengthening phase are such that 7075 is a very quench sensitive alloy, meaning that if there is a delay between the solutionizing and quenching of the part, or a slow quench, the mechanical properties will decrease sharply [6,7]. 7075 is also very sensitive to iron impurities, as the intermetallic phases made with iron act as stress concentrators reducing the overall strength of the casting.…”
Section: Solidificationmentioning
confidence: 99%